PENGEMBANGAN BAHAN AJAR IPA KELAS V SEKOLAH DASAR MENGGUNAKAN MULTIMEDIA INTERAKTIF BERBANTUAN ANIMASI - Puspa Tri Wardani; Mijahamuddin Alwi; Arif Rahman Hakim (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This study aim in other to result teaching material used interactive multimedia based animation on science subject especially on water recycled cycle in academic year 2019/2020. The development learning model on this study was Borg and Gall model. This study was conducted into some steps, they are (1) the need analysis step; (2) design step; (3) creating and validating product step; (4) product revision step; (5) try out product step; (6) final product revision step. The subject of this study was fifth grade student of MI NW No, 02 Kelayu Selatan. Based on the product validation which carried out by the expert team showed that the score of the sight experts was 61, on average of 4.69 with “excellent category” on the score board X > +1,80SBi. Whereas the score of material and language were 35 with an average of acquisition of 5 with excellent category score on the score board X > +1,80SBi. The result showed, the result of field try out test was 97% which student responded “yes”, while the result of study acuity was 85%. Based on the result it can be concluded that the teaching material which developed by the researcher was very worthy of using for science-learning activities in recycled cycle materials.